Upaya Guru BK Dalam Membiasakan Budaya 5S (Sapa, Salam, Senyum, Sopan, dan Santun) pada Siswa di SMK 3 Perguruan Cikini, Jakarta Selatan - Kinanti Ayuningtiyas; Nurmawati Nurmawati (LPPM Institut Pendidikan Nusantara Global, 2025)
This study discusses the efforts of Guidance and Counseling (BK) teachers in instilling the 5S culture (Smile, Greet, Salute, Polite, and Courteous) among students at SMK 3 Perguruan Cikini, South Jakarta. The positive attitudes instilled through school culture play a crucial role in character formation. Although the implementation of the 5S culture in this school has been carried out, observations indicate that some students have not maximally adopted this culture. BK teachers play a strategic role in implementing this program through various strategies, including education, collaboration with other teachers, and positive communication approaches. The results show that while there has been progress, challenges in consistency and program effectiveness still need to be addressed to achieve the desired character formation goals.